TEACHING VARIATIONS BY TEACHERS TO INCREASE STUDENT MOTIVATION IN LEARNING ENGLISH AT SMPN 1 RANTETAYO - Rielsa Tirangka (Publikasi dan UKI Press UKI Toraja., 2023)
This research discussed The Teaching Variations by Teachers To Increase Student Motivation In Learning English at SMPN 1 Rantetayo’. The goal of this research is to find out the what are the variations by teachers to increase students’ motivation in learning English at SMPN 1. In this research, the researcher used a qualitative method. The participants of the research were all the English teachers at the school. To collect the data, the researcher used observations, interview, and documentation as research instruments. The purposes of this study to find out what are the teaching variations by teachers to increase students’ motivation in learning English. In this study, researcher used qualitative methodology by involving students of SMPN 1 Rantetayo and English teachers as respondents. The researcher used interview, observation, and documentation to collect the data. Then, to nalyzed the data using the theory of Sugiono (2017:294). The result from this research is that the teachers at SMP 1 Rantetayo apply several variations to attract students' attention so that students are more motivated in the learning process, especially English language learning. The variation used are; Teaching Style Variation, Media Variation, and interaction Variation directly between teachers and students.